Original paperPharmacological treatment and qualification for invasive treatment after coronary angiography in patients with stable angina according to the presence of diabetes - Kobus, Grażyna; Tomaszuk-Kazberuk, Anna; Bachórzewska-Gajewska, Hanna; Kuleszyńska, Agnieszka; Małyszko, Jolanta; Dobrzycki, Sławomir; J. Musiał, Włodzimierz (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2012)
Aim : The aim of the study was to assess pharmacological treatment and qualification for invasive treatment after coronary angiography in patients with stable coronary artery disease (CAD) according to the presence of diabetes and the methods of treatment in diabetes. Material and methods : In this retrospective study we enrolled 403 patients with stable CAD. The patients were divided into 2 groups: patients with hypertension and diabetes and a control group with hypertension. Additionally the patients with diabetes were divided into 2 groups: one group treated with insulin and the second group treated with oral glucose lowering agents. Results : We enrolled 403 patients (mean age 65.4 ±9.6 years old). Hypertension was diagnosed in 335 patients (83.1%) and diabetes in 96 patients. β-Blockers were used by 92%, acetylsalicylic acid (ASA) by 94%, statins by 93.5%, angiotensin-converting enzyme inhibitors (ACEI) by 84%, diuretics by 46% and clopidogrel by 55.6% of the patients. One hundred and ninety-three patients (47.9%) were qualified for percutaneous coronary intervention (PCI) and 51 patients (12.7%) for coronary artery bypass grafts (CABG). Among patients with diabetes 31 (7.7%) were using insulin while 65 were using oral agents. 15.6% of the patients with diabetes and 13.3% without diabetes were scheduled for CABG, while 49.0% and 46.4%, respectively, were scheduled for PCI. 58.1% of the patients using insulin and 44.6% using oral agents were scheduled for PCI. Coronary artery bypass grafts was recommended for 16% and 15% of the patients (p = NS). Conclusions : Patients with hypertension and CAD are treated according to current guidelines. Qualification for invasive treatment in the group with and without diabetes was similar. In the group with diabetes patients treated with insulin were more often qualified for invasive treatment (especially PCI) as compared to patients treated with oral agents.